Density functional calculation for the first and second harmonic generation of the chalcopyrite Ga2AsSb - Reshak, Ali Hussain; Ouahrani, T.; Khenata, R.; Otero-de-la-Roza, A.; Luana, V.; Baltache, H. (Elsevier B. V., 2011)
Link to publisher's homepage at http://www.elsevier.com/